DEMAND ON ADSORPTIVE INTESTINAL PREPARATIONS ANALYSIS USING A VYSHKOVSKY'S INDEX - A. V. Bondarev; E. T. Zhilyakova (Фармация и фармакология (Пятигорск))
The article presents the results of Vyshkovsky's index use for adsorptive intestinal preparations demand analysis. We have also considered a possibility of a new adsorption intestinal preparation launch on the Russian pharmaceutical market